The Phormidolide Biosynthetic Gene Cluster: A trans‐AT PKS Pathway Encoding a Toxic Macrocyclic Polyketide. Issue 2 (23rd December 2015) - Bertin, Matthew J.; Vulpanovici, Alexandra; Monroe, Emily A.; Korobeynikov, Anton; Sherman, David H.; Gerwick, Lena; Gerwick, William H.
Abstract: Phormidolide is a polyketide produced by a cultured filamentous marine cyanobacterium and incorporates a 16‐membered macrolactone. Its complex structure is recognizably derived from a polyketide synthase pathway, but possesses unique and intriguing structural features that prompted interest in investigating its biosynthetic origin. Stable isotope incorporation experiments confirmed the polyketide nature of this compound. We further characterized the phormidolide gene cluster ( phm ) through genome sequencing followed by bioinformatic analysis. Two discrete trans ‐type acyltransferase ( trans ‐AT) ORFs along with KS‐AT adaptor regions (ATd) within the polyketide synthase (PKS) megasynthases, suggest that the phormidolide gene cluster is a trans ‐AT PKS. Insights gained from analysis of the mode of acetate incorporation and ensuing keto reduction prompted our reevaluation of the stereochemistry of phormidolide hydroxy groups located along the linear polyketide chain. Abstract : By integrating information gained from stable isotope incorporation studies with bioinformatic analysis of genome data, the biosynthetic pathway of phormidolide, a toxic cyanobacterial polyketide, was identified and characterized. The biosynthesis occurs through the action of a trans ‐AT system and features several interesting deviations from typical modular PKS pathways.